Sex and gender considerations in cross-cultural traumatic stress studies - Rachel Langevin; Sophie Beaudette; Dany Laure Wadji; Sara Abou Chabake; Carolina Gonzalez; Dan Jenkins; Safa Kemal Kaptan; Jessica Lambert; Tilahun Belete Mossie; Rosario Spencer (European Journal of Psychotraumatology, 2024)
Following the 1st Conference of the Global Collaboration on Traumatic Stress, the consortium committed to systematically integrating sex and gender considerations in their endeavours, which aligns with the European Journal of Psychotraumatology's Gender Policy. This initiative is vital for understanding trauma's complex impacts, but also presents significant challenges in cross-cultural research. This letter, co-authored by researchers from across the globe, outlines these challenges and proposes mitigation strategies. First, definitions of sex and gender are provided from a Western perspective, while acknowledging cultural differences in these concepts. Second, the relevance of integrating sex and gender considerations in traumatic stress studies is briefly described. Third, cultural distinctions and legal contexts shaping the understanding and inclusion of these concepts, with non-Western and low-to-middle income regions facing significant legal and ethical obstacles are highlighted. Methodological challenges including measurement, recruitment, and statistical modelling are discussed, followed by recommendations including participatory approaches that involve members of the community, including sexual and gender minority individuals, as possible, throughout the research process, conducting risk analyses, employing sensitive quantitative and qualitative methods, and ensuring clear reporting and participant protection. To conclude, with this letter, we hope to instigate dialogue and foster innovative approaches to incorporating sex and gender considerations in cross-cultural studies of traumatic stress. Addressing these considerations is essential for ethical, meaningful research that respects and safeguards diverse experiences.